International Financial Statistics, December 2016. (International Financial Statistics; International Financial Statistics ;, 2016)
The December 2016 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. This issue presents countries newly reporting monetary data for Norway using the standardized report forms. In this issue, the following changes have been made: Changes to the group aggregates aligned with those published in the IMF's World Economic Outlook (WEO): (1) Move of China, P. R.: Macao (546) out of Emerging and Developing Asia (505) to Advanced Economies (110); (2) Move of Bolivia (218) and Colombia (233) out of Export Earnings: Nonfuel economies (092) to Export Earnings: Fuel economies (080). Removal of China, P. R.: Macao (546), Latvia (941), and Lithuania (946) out of Export Earnings: Nonfuel economies (092). For countries where multiple exchange rates are in effect, Fund staff estimates of weighted average exchange rates are used in many cases.